Executive functioning, ecological and biological predictors: Longitudinal evidence - Walker, Sue; Shahaeian, Ameneh; Harrison, Linda (My University, 2014)
To be able to perform as successful adults children need to develop certain skills throughout the early years. Specific attention during this period is made to flexibility, creativity, self-control and discipline, all of which are seen to be part of executive functioning (Diamond & Lee, 2011). A large body of research has shown that having a higher level of executive functioning is related to better school outcomes (Bierman, Nix, Greenberg, Blair, & Domitrovich, 2008; Blair & Razza, 2007); however, longitudinal evidence for very early predictors of executive functions and related skills, such as self-regulation, is scarce (Bernier, Carlson, & Whipple, 2010). The current study aims to look at early predictors of self-regulation from birth to age 6-7years. Participants were 3418 children in the Birth cohort of the Longitudinal Study of Australian Children (LSAC). Parent interview, teacher questionnaire and child assessment data from the first four waves of LSAC (2004 – 2010) were used in the analyses. Executive functioning skills were assessed through a teacher-rated measure of behavioural self-regulation at Wave 4 (age 6-7 years). Predictors were measures of children’s sex, ethnicity, temperament and the family environment, including socio-economic position (SEP), quality of parent-child interaction, and the quality of the home learning environment. Results showed that child sex, ethnicity and temperament and family SEP were better predictors of self-regulation/executive functioning in the classroom than the quality of the parent-child relationship. The quality of the home learning environment, specifically, the number of books in the home and the number of minutes the child enjoyed being read to, were also significant predictors. In the final model, explaining 9.3% of the variance, the best predictor was child sex (female, B = .241, p < .001), followed by SEP (B= .161, p< .001), the number of books in the home (B = .040, p < .05) and the number of minutes the child enjoyed being read to (B = .039, p < .05). Results indicate that executive functioning skills can be enhanced through improving the quality of the home learning environment, specifically by having more books in the home and reading to the child in the early childhood years.
Keywords: Children -- Outcomes; Child Development; Children -- Early childhood; Childhood and child development; Child Development; Children; Outcomes; Early childhood; Childhood and child development